Прогностичні чинники акушерсько-перинатальних завершень у жінок, які мешкають в умовах природного йодного дефіциту - Паєнок, О. С.; Паньків, В. І.; Костів, М. О. (Clinical Endocrinology and Endocrine Surgery, 2012)
Developed method of predicting obstetric complications in women with thyroid gland pathology allows to select the most informative risk factors for the development of obstetric complications and on this basis to suggest a prediction algorithm with an accuracy of 86 % and appropriate treatment and preventive measures.